Universality of vortex ring decay in the left ventricle. (16th April 2020) - Brindise, Melissa C.; Meyers, Brett A.; Vlachos, Pavlos P.
Abstract: We present clinical measurements and a theoretical model for the decay of the left ventricular (LV) vortex ring. Previous works have postulated that the formation of the vortex ring downstream of the mitral annulus is affected by LV diastolic impairment. However, no previous works have considered how the strength of the vortex ring will decay inside the ventricle after its formation. Although the vortex ring formation relates to the very initial stage of the filling, the decay process is governed by a large portion of the diastolic time and will be affected by the interaction of the ventricle walls and the vortex ring. Here we used in-vivo measurements and presented a mechanistic model to calculate the evolution of the vortex ring strength and predict the rate of vortex ring decay within the left ventricle. The results demonstrated the actual circulation decay rate was universal, remaining nearly unchanged across all subjects of varying LV geometry or diastolic function. Furthermore, using the model-predicted circulation decay rate, differentiation between normal and abnormal filling was observed.